Pelatihan Penulisan Karya Ilmiah Bagi Guru-Guru Sekolah Dasar Katolik Gugus Kabalidana Kecamatan Wewewa Barat Kabupaten Sumba Barat Daya, Propinsi NTT - Daindo Milla; Kristoforus Dowa Bili (Unram Journal of Community Service, 2022)
Community service activities at the elementary school level of the kabalidana cluster, West Wewewa District, Southwest Sumba Regency, East Nusa Tenggara Province are an activity for the community carried out by the PGSD Lecturer Team from STKIP Weetebula. This activity aims to grow and increase teachers' understanding of the importance of writing scientific papers through training in writing scientific papers. This activity was held on December 13-14, 2020 and took place at SDK Pero, Pero village, West Wewewa District, Southwest Sumba Regency, NTT. This training was attended by 2 Catholic Elementary Schools with a total of 38 participants who attended who were teachers. The service activity was carried out within two days and continued until now through online media, namely via WhatsApp where the first day delivered materials on how to write scientific papers correctly in accordance with the stages and the second day carried out the practice of writing scientific papers for Catholic Elementary Schools teachers. In the implementation of the practice, there are some teachers who still do not understand how to write scientific papers, especially the formulation of problems to research methods. This is evidenced by the provision of questionnaires filled by training participants with one of the aspects that are filled in is formulating a problem then determining how to solve it